Study on Structural Service Performance of Heavy-Haul Railway Tunnel with Voided Base. (11th October 2018) - Zhang, Zhiqiang; Zeng, Bowen; Dai, Chaolong; He, Wanping
Abstract : The structural design of heavy-haul railway tunnels still follows the design method of ordinary railway tunnels. Most of them do not take into account the influence of large axle load of 30 t or more, let alone such problems as void of surrounding rock under long-term dynamic loads. In order to analyze the dynamic response of heavy-haul railway tunnels under long-term reciprocating cyclic dynamic loads, considering the factors such as axle load of vehicle body, unsprung mass, and track irregularity, the vibration load time-history curve of heavy-haul railway trains is determined, the three-dimensional dynamics coupling model of dynamic load-tunnel-surrounding rock is established, and the fatigue life of the structure under different void conditions is analyzed based on the S-N curve of concrete. According to the study, the loading, unloading, and vibration caused by train passing will lead to fluctuations in the vertical displacement response of the monitoring point. The peaks and valleys of the response time-history curve correspond to the effect of the train wheels rolling through. When the void is 6 m wide and 10 cm thick, the vertical displacement of the inverted arch is increased by about 9 times, the peak velocity of the inverted arch is increased by about 3.8 times, and the maximum principal stress is increased by about 47.3%, compared with the condition without void. With the same void thickness, the vertical displacement and velocity curves of the inverted arch vary significantly with the increase of the void width. The width of the base void has a significant effect on the fatigue life of the structure of heavy-haul railway tunnels. Based on the operation requirement of 100-year service life, the ultimate void width is 2 m.